Superior strength-ductility synergy of wire-arc directed energy deposited Mg-Al-Si alloys mediated by sub-rapid solidification - Qifei Han; Yueling Guo; Jinlong Hu; Rui Fu; Yangyu Yan; Changmeng Liu (Journal of Magnesium and Alloys)
Here we propose to employ wire-arc directed energy deposition (WA-DED) to tune the microstructure and the mechanical property of Mg-Al-Si alloys, on the basis of its sub-rapid solidification effect. According to finite element analysis, WA-DED shows higher cooling rate than conventional casting, reaching 598.3 K/s for Mg-Al-Si alloy, and the lower heat input, the larger cooling rate of WA-DED. Significant microstructure refinement is thus achieved, with reduced grain size and Mg2Si particle diameter. The transition from hypereutectic to fully eutectic microstructure is triggered by reducing the heat input. Compared with the as-cast alloy, WA-DED alloys demonstrate higher ultimate tensile strengths (UTS) at both room- and high-temperature (150 ℃) properties, increasing by 50.1% and 30.3%, respectively. The superior strength-ductility synergy for Mg-Al-Si alloys results from the microstructure tuning via sub-rapid solidification of WA-DED.